Professional context of teaching reading to foreign economics students - Olena Titarenko; O. Kopylova (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки)
The article continues a series of studies dedicated to teaching Ukrainian-language reading skills to foreign students specializing in economics. It underscores the significance of achieving communicative objectives in education to ensure that foreign students in higher education comprehend their specialty and various forms of Ukrainian-language communication. However, the initial level of text comprehension among students at the onset of the main stage of learning is insufficient to effectively support the educational process in Ukrainian higher education institutions within their chosen specialties.